Controlling the Use of Parliamentary History - Evans, Jim (Journal of Malaysian and Comparative Law, 2019)
The use of parliamentary history to assist the interpretation of statutes has now been accepted in many countries of the Commonwealth, including Singapore and Malaysia. I am not sure, however, that Commonwealth lawyers yet have a full sense of the likely significance of the change.